A smoothing agent for enhancing the wear resistance of textile sizing and a preparation process thereof

CN122942331APending Publication Date: 2026-10-20WUJIANG TIANLI POLYMER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611288800.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

这类平滑剂与丙烯酸酯浆料相容性有限,在储存和使用过程中容易发生迁移、析出或分层,导致上浆不均匀,且耐磨持久性较差,无法在高密度织物长时间的高速织造中维持稳定的平滑保护效果

Benefits of technology

1、通过将甲基丙烯酸十八酯、丙烯酸丁酯、甲基丙烯酸甲酯、苯乙烯、丙烯酸和甲基丙烯酸以特定比例组合共聚,在同一聚合物分子链中集成了长链烷基的内润滑功能、软单体的柔顺成膜功能、硬单体的刚性支撑功能以及羧基单体的物理交联功能。四种功能组分相互弥补单一使用时存在的性能短板,长链润滑单体缺乏内聚强度,软硬单体的范德华力不足以抵御持续摩擦下的链段滑移,羧基单体的氢键交联网络则弥补了这一不足。上述组分协同作用,使浆膜兼具持久的低摩擦系数、良好的柔韧性和足够的结构完整性,共同提升了处理后织物的耐磨性和力学性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This application relates to a smoothing agent for enhancing the abrasion resistance of textile sizing agents and its preparation process, belonging to the field of textile sizing auxiliary technology. The raw materials for preparation include mixed monomers, reaction media and auxiliaries, neutralizing agents, dilution water, and post-treatment auxiliaries. The mixed monomers comprise the following components in the following mass percentages: 45-55% octadecyl methacrylate, 4-8% acrylic acid, 16-22% methacrylic acid, 1-4% styrene, 8-12% methyl methacrylate, and 10-16% butyl acrylate. This application overcomes the shortcomings of single-component performance bias by copolymerizing the above monomers in a specific ratio, simultaneously introducing internal lubrication, flexible film formation, rigid support, and physical cross-linking functions into the same molecular chain, resulting in a sizing film with both low friction coefficient and structural integrity. By measuring the content of impurities in the raw materials and residual monomers in the recovered fraction and incorporating them into the formulation for stoichiometric deduction, a closed-loop material process is formed, improving the comprehensive utilization rate of raw materials and batch consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of textile sizing agents, and in particular to a smoothing agent for enhancing the abrasion resistance of textile sizing agents and its preparation process. Background Technology

[0002] Currently, high-end fashion and functional clothing made from imitation silk, imitation suede, and high-density fabrics have become mainstream in the market. The synthetic fiber filaments used in these garments are extremely fine, and the fibers themselves are quite delicate. During high-speed air-jet weaving, the warp yarns must withstand repeated friction from components such as heddles, reeds, and guide rollers. Fine denier filaments are highly susceptible to pilling, single-filament breakage, and even end breakage due to friction, severely restricting weaving efficiency and product quality. To ensure the smooth weaving of high-density fabrics, the sizing agent must possess excellent smoothness and abrasion resistance to form a protective film on the fiber surface, minimizing the coefficient of friction and resisting mechanical wear.

[0003] Acrylic sizing agents are widely used in textile sizing due to their excellent adhesion and film-forming properties to synthetic fibers. However, the smoothing properties of acrylic copolymer sizing films still cannot fully meet the requirements of high-speed weaving. The surface friction coefficient after film formation is relatively high, and the film is prone to breakage under continuous mechanical friction, resulting in the yarn losing its protection. To fundamentally improve the smoothness and abrasion resistance of sizing agents, it is usually necessary to add specialized smoothing agents to acrylic sizing agents or slurries. By introducing friction-reducing components, the shortcomings of the main sizing agent are compensated for. This has become an industry-standard practice that balances cost and performance optimization.

[0004] Currently, traditional textile smoothing agents mostly use wax-based or silicone emulsions, which are added to the sizing system through physical blending. These smoothing agents have limited compatibility with acrylic sizing agents and are prone to migration, precipitation, or stratification during storage and use, resulting in uneven sizing and poor abrasion resistance. They cannot maintain a stable smoothing and protective effect during long-term, high-speed weaving of high-density fabrics. Summary of the Invention

[0005] To address the aforementioned issues, this application provides a smoothing agent for enhancing the abrasion resistance of textile sizing agents and its preparation process.

[0006] This application provides a smoothing agent for enhancing the abrasion resistance of textile sizing agents and its preparation process, which adopts the following technical solution: In a first aspect, this application provides a smoothing agent for enhancing the abrasion resistance of textile sizing agents, employing the following technical solution: A smoothing agent for enhancing the abrasion resistance of textile sizing agents, comprising raw materials including mixed monomers, reaction media and auxiliaries, neutralizing agents, dilution water and post-treatment auxiliaries, wherein the mixed monomers comprise the following components in weight percentage: Octadecyl methacrylate 45-55% Acrylic acid 4-8% 16-22% methacrylic acid Styrene 1-4% Methyl methacrylate 8-12% Butyl acrylate 10-16%; The sum of the mass percentages of all components is 100%.

[0007] Preferably, the mixed monomers comprise the following components in weight percentage: 50% octadecyl methacrylate 6% acrylic acid 18-20% methacrylic acid styrene 2-3% 8-10% methyl methacrylate Butyl acrylate 13-14%; The sum of the mass percentages of all components is 100%.

[0008] While increasing the amount of a single type of monomer can enhance the specific properties of the film, it often leads to the deterioration of other essential characteristics. If smoothness is provided solely by a high content of long-chain alkyl esters, the cohesive strength of the film is insufficient; if hard monomers are simply added to improve film strength, flexibility decreases, and microcracks are easily generated during friction; if excessive hydrophilic monomers are introduced to improve water dispersibility, the adhesion of the film to hydrophobic fibers decreases. This application combines octadecyl methacrylate, butyl acrylate, methyl methacrylate, acrylic acid, methacrylic acid, and styrene in a specific ratio, overcoming the shortcomings caused by the aforementioned single-performance orientation. The long-chain alkyl side chains of octadecyl methacrylate form a lubricating layer within the polymer, improving the smoothness and abrasion resistance of the treated yarn. Butyl acrylate, as a soft monomer, enhances the flexibility and film-forming continuity of the slurry film, allowing it to deform in tandem with the yarn during friction and stretching, thus increasing elongation at break and reducing the coefficient of variation of breaking strength. Methyl methacrylate and styrene, as hard monomers, provide rigid chain segments, improving the cohesive strength of the slurry film and thus enhancing the breaking strength of the yarn. The combination of these soft and hard monomers with lubricating monomers gives the slurry film a combination of smoothness, flexibility, and strength, but the cohesive energy density remains limited when relying solely on van der Waals forces and chain entanglement.

[0009] To further enhance the structural integrity of the slurry film, acrylic acid and methacrylic acid introduced into the mixed monomers provide carboxyl functional groups. Hydrogen bonding between carboxyl groups and the subsequent neutralization-formed ionic clusters construct a physical crosslinking network between polymer chains, compensating for the insufficient cohesive energy density when relying solely on van der Waals forces. The carboxyl groups of acrylic acid are directly attached to the main chain, providing effective hydrophilicity and crosslinking sites; the α-methyl groups of methacrylic acid create steric hindrance, moderately inhibiting the reactivity of the carboxyl groups and regulating chain segment rigidity, avoiding the brittleness of the slurry film caused by excessively high crosslinking density when using acrylic acid alone. When these six monomers are copolymerized within a defined mass ratio range, four functions—long-chain lubrication, flexible film formation, rigid support, and physical crosslinking—are integrated into the same polymer molecular chain, overcoming the shortcomings of single-component single-function or performance bias, and improving the abrasion resistance and smoothness of the yarn.

[0010] Preferably, the reaction medium and auxiliaries comprise components comprising a percentage of the total mass of the monomers below: 31-33% of industrial alcohol is recovered. Fatty alcohol polyoxyethylene ether penetrants 7-15% Isooctyl alcohol 1-5% n-Dodecanethiol 0-0.02% tert-dodecyl mercaptan 0.005-0.02% Water 2.5-3.5% Benzoyl peroxide 1.2-1.6%.

[0011] In the aforementioned monomer copolymerization process, recycled industrial alcohol, used as a reaction solvent, reduced the viscosity of the polymerization system. Its chain transfer effect helped control the polymer molecular weight, avoiding problems such as poor slurry permeability and rough film formation caused by excessively large molecular weight. Fatty alcohol polyoxyethylene ether penetrants reduced the interfacial tension between hydrophobic monomers and the solvent, ensuring uniform dispersion of monomers such as octadecyl methacrylate, guaranteeing the homogeneity of the copolymer composition, and thus improving the consistency of breaking strength among different yarn samples. Isooctyl alcohol, as a co-solvent, adjusted the system compatibility, reducing excessive coiling or local precipitation of polymer chains in the solvent, resulting in a smoother slurry film spreading on the yarn surface. The different chain transfer constants of n-dodecyl mercaptan and tert-dodecyl mercaptan allow for precise control of molecular weight distribution, giving the polymer both good flowability and sufficient mechanical strength. Benzoyl peroxide stably initiated polymerization in this medium system, making the copolymer solution uniform and stable, providing a foundation for obtaining a smoothing agent with batch-stable performance.

[0012] Preferably, the neutralizing agent includes ammonia.

[0013] Ammonia water acts as a neutralizing agent, reacting with the carboxyl groups on the copolymer chains to convert some carboxylic acid groups into ammonium carboxylate salts. This imparts water dispersibility to the polymer, allowing it to adhere uniformly to the yarn surface during dilution and sizing. Controlling the degree of neutralization achieves a balance between hydrophilicity and cohesion in the sizing film. The film spreads evenly on the yarn surface and is less prone to swelling and weakening due to excessive hydrophilicity, thus improving the integrity of the sizing film's coating and its mechanical protection effect on the yarn.

[0014] Preferably, the post-treatment aids include defoamers and bactericides.

[0015] The addition of defoamers eliminates bubbles generated during high-speed stirring and dilution in the production process, avoiding pinhole defects in the slurry film caused by bubble rupture, and improving the continuity of the slurry film and the uniform coating effect on the yarn. The addition of bactericides prevents pH drop and polymer degradation caused by microbial growth during product storage, ensuring that the product maintains its original smoothness and film-forming properties even after long-term storage.

[0016] Secondly, this application provides a preparation process for a smoothing agent used to enhance the abrasion resistance of textile sizing agents, employing the following technical solution: A process for preparing a smoothing agent to enhance the abrasion resistance of textile sizing agents includes the following steps: (1) Add the reaction medium and auxiliaries into the reaction apparatus, add the mixed monomers, seal and start stirring, and control the stirring speed to 20-30 rpm; (2) After heating until bubbles appear on the surface of the liquid material in the reaction apparatus, stop heating and use the heat of polymerization to allow the system to heat up naturally. Keep the reaction at room temperature for 2.5-3.5 hours. (3) After the heat preservation reaction is completed, adjust the stirring speed to 40-50 rpm, add the neutralizing agent to carry out the neutralization reaction. After the addition is completed, react for 20-40 minutes, and the degree of neutralization is 65-73%. (4) After the neutralization reaction is complete, dilute with water in batches, stirring well after each addition; (5) After dilution, cool down, add post-treatment aids and stir evenly, filter and discharge to obtain a smoothing agent for enhancing the abrasion resistance of textile sizing agents.

[0017] In the preparation process of the smoothing agent, the process conditions and operation sequence of each step are coordinated to ensure the final product performance. A low stirring speed is used during the feeding stage to ensure uniform mixing of the monomer and reaction medium while preventing premature decomposition of the initiator, laying the foundation for subsequent uniform polymerization. The adiabatic heating process utilizes the exothermic reaction itself to match the initiator decomposition rate with the chain growth rate, resulting in a stable and controllable polymerization process and a concentrated molecular weight distribution of the obtained polymer. After the heat treatment, the stirring speed is increased and a neutralizing agent is added at a uniform rate to ensure uniform ammonium salting of carboxyl groups within a preset range, preventing localized over-alkaliness that could lead to polymer precipitation. Diluent is added in batches to gradually transform the system from water-in-oil to oil-in-water. After each batch of water is added, thorough stirring ensures complete hydration and phase adjustment of the polymer chains, preventing sudden precipitation of polymer and the formation of gel particles during phase inversion, thus improving the continuity of the film after product formation. After cooling, post-treatment aids are added and the product is filtered to remove trace gel impurities, ensuring the product's storage stability and batch-to-batch performance consistency.

[0018] Preferably, in step (2), the system is naturally heated to 80-98°C by utilizing the exothermic polymerization. When the temperature drops below 80°C, the system is heated for 1-2 minutes.

[0019] The exothermic polymerization process allows the system to naturally heat to 80-98℃. Utilizing the exothermic peak of the reaction itself promotes chain transfer and self-regulates the polymer molecular weight, avoiding the problems of excessively high molecular weight and widened distribution caused by external heating throughout the process, thus improving the consistency of the polymer molecular weight distribution. When the temperature drops below 80℃, a short-term heating is applied to compensate for the decrease in conversion rate caused by insufficient exothermic reaction in the later stages, ensuring complete monomer conversion. This temperature control method results in stable product viscosity between batches, improving batch consistency.

[0020] Preferably, in step (4), dilution water is added in 3-5 batches. After the first batch is added, the mixture is stirred for 55-65 minutes, and after the second and subsequent batches are added, the mixture is stirred for 25-35 minutes.

[0021] Diluent was added in 3-5 batches, with a longer stirring time after the first batch and a shorter stirring time for subsequent batches. This allowed the water content of the system to gradually increase during the phase inversion process, ensuring sufficient time for the polymer chains to complete hydration and phase adjustment after each batch of water addition. This prevented sudden polymer precipitation and gel formation caused by excessively high local water concentrations. This gradient dilution method improved the uniformity of phase inversion and the integrity of the film formation. After yarn treatment, surface defects in the slurry film were reduced, and the coefficient of variation of abrasion resistance and tensile strength were improved simultaneously.

[0022] Preferably, the water in the reaction medium and the auxiliary agent in step (1) comes from the fraction obtained by fractionation, and the fraction includes water and methacrylic acid; the preparation process also includes determining the content of methacrylic acid in the fraction, directly recycling the fraction back into the reaction system, the methacrylic acid in the fraction participating in copolymerization as a supplementary monomer, and reducing the amount of methacrylic acid added in the formulation accordingly based on the determination results.

[0023] The aqueous fraction recovered after polymerization is directly reused as the reaction medium, eliminating the need for treating wastewater containing organic matter. Simultaneously, the content of entrained methacrylic acid is measured and included in the total amount of carboxyl monomers in the formulation, with a corresponding deduction for the amount of fresh methacrylic acid added. This allows monomers that would otherwise be lost with the wastewater to re-enter the polymerization chain, achieving resource recovery of monomers. This method maintains batch-to-batch stability of carboxyl content in the reaction system without increasing separation and purification costs, improves the consistency of mechanical properties of fabrics treated with the product, and forms a closed-loop cycle of water and monomers.

[0024] Preferably, the octadecyl methacrylate in the mixed monomers in step (1) is a self-synthesized product, and the octadecyl methacrylate contains methacrylic acid; the preparation process further includes determining the content of methacrylic acid in the octadecyl methacrylate and including it in the total amount of methacrylic acid in the formula, thereby reducing the amount of methacrylic acid in the formula accordingly.

[0025] By directly incorporating self-synthesized octadecyl methacrylate into the reaction without rigorous deacidification, the separation and purification costs, material consumption, and energy consumption associated with the esterification product purification process are eliminated. The content of entrained methacrylic acid is measured and included in the total formulation for deduction, allowing this residual monomer from upstream synthesis to be effectively absorbed as a copolymer component during the polymerization step, thus reducing the purchase and input of fresh methacrylic acid. This method, in conjunction with solvent recovery deduction, forms a closed-loop material system covering both upstream raw material impurities and downstream recoveries, improving the comprehensive utilization rate of raw materials and making the production process both economical and clean.

[0026] In summary, this application includes at least one of the following beneficial technical effects: 1. By copolymerizing octadecyl methacrylate, butyl acrylate, methyl methacrylate, styrene, acrylic acid, and methacrylic acid in a specific ratio, the internal lubrication function of long-chain alkyl groups, the film-forming flexibility of soft monomers, the rigid support function of hard monomers, and the physical crosslinking function of carboxyl monomers are integrated into the same polymer molecular chain. These four functional components compensate for the performance shortcomings that exist when used individually. The long-chain lubricating monomers lack cohesive strength, and the van der Waals forces of both soft and hard monomers are insufficient to resist chain segment slippage under continuous friction. The hydrogen-bonded crosslinking network of the carboxyl monomers compensates for this deficiency. The synergistic effect of these components gives the film a durable low coefficient of friction, good flexibility, and sufficient structural integrity, collectively improving the abrasion resistance and mechanical properties of the treated fabric.

[0027] 2. The methacrylic acid carried in the self-synthesized octadecyl methacrylate and the residual methacrylic acid in the fractionated recovery water are included in the total amount of the formulation for stoichiometric deduction after content determination. This reduces the amount of fresh methacrylic acid required, eliminates the need for strict deacidification of upstream esterification products and treatment of wastewater containing organic matter, lowers separation and purification costs and reduces material and energy consumption. Residual monomers originally present in raw material impurities and downstream recoveries are effectively absorbed as copolymer components, forming a closed-loop material system covering both upstream and downstream processes, and improving the comprehensive utilization rate of raw materials. This deduction method, in conjunction with the molecular weight self-regulation of adiabatic polymerization and the phase inversion control of gradient batch dilution, ensures that the chemical composition, molecular weight distribution, and emulsion particle size of the copolymer remain stable across different production batches, guaranteeing batch-to-batch consistency of the mechanical properties of the yarn after treatment. Detailed Implementation

[0028] This application discloses a smoothing agent for enhancing the abrasion resistance of textile sizing agents and its preparation process. Unless otherwise specified, all raw materials used in this application are commercially available. The following detailed description, in conjunction with embodiments, further illustrates this application: Raw material specifications: Octadecyl methacrylate (CAS No.: 32360-05-7), acrylic acid (CAS No.: 79-10-7), methacrylic acid (CAS No.: 79-41-4), styrene (CAS No.: 100-42-5), methyl methacrylate (CAS No.: 80-62-6), butyl acrylate (CAS No.: 141-32-2), benzoyl peroxide (CAS No.: 94-36-0), isooctanol (CAS No.: 104-76-7), tert-dodecyl mercaptan (CAS No.: 25103-58-6), n-dodecyl mercaptan (CAS No.: 112-55-0), fatty alcohol polyoxyethylene ether penetrant R803A was purchased from Haian Petrochemical, high-temperature defoamer X-18C was purchased from Nanjing Sixin, and MBS bactericide was purchased from Foshan Liyuan Chemical Co., Ltd. Example 1

[0029] The mixture was prepared according to a total monomer weight of 1800 kg. The monomers consisted of the following components by mass percentage: 50% octadecyl methacrylate, 6% acrylic acid, 20% methacrylic acid, 2% styrene, 8% methyl methacrylate, and 14% butyl acrylate. Octadecyl methacrylate was a self-synthesized product, and its mass content was measured to be 82.15%, while the mass content of methacrylic acid was 17.85%. This was included in the total amount of methacrylic acid in the formulation, and the amount of methacrylic acid added was reduced accordingly. The reaction medium and auxiliaries were components accounting for the following percentages of the total monomer mass: 32% recovered industrial alcohol, 15% fatty alcohol polyoxyethylene ether penetrant, 1% isooctanol, 0.02% tert-dodecyl mercaptan, 3% water, and 1.4% benzoyl peroxide. The fatty alcohol polyoxyethylene ether penetrant was model R803A. The water was obtained from the fractionation product, and the water content in the fractionation product was measured. The content of methacrylic acid is as follows: water content is 55.63% by mass, and methacrylic acid content is 44.37% by mass. The fractionated product is directly recycled into the reaction system. The methacrylic acid in the fractionated product participates in copolymerization as a supplementary monomer. The amount of methacrylic acid added to the formula is reduced accordingly based on the test results. The neutralizing agent is ammonia water. 351 kg of ammonia water is diluted with 1000 kg of process water before use. The dilution water is added in 4 batches. The dilution water is hot process water. The amount of dilution water added is 1000 kg for the first batch, 1500 kg for the second batch, 1800 kg for the third batch, and 1000 kg for the fourth batch. The post-treatment aids are defoamer and bactericide. The defoamer is high-temperature resistant defoamer X-18C. 12 kg of high-temperature resistant defoamer X-18C is diluted with 80 kg of process water and stirred until completely dissolved before use. The bactericide is MBS bactericide. 12 kg of bactericide is diluted with 50 kg of process water and stirred evenly before use.

[0030] (1) Check whether the cooling tower is normal and whether the condenser outlet water is normal. If it is normal, start the reaction, put the reaction medium and additives into the reactor, mix the monomers in the monomer mixing tank, add the mixed monomers into the reactor, rinse the pipeline of the 30kg industrial recovered alcohol in the reaction medium and additives in the monomer mixing tank, put the rinse material into the reactor, seal the reactor, start the reactor stirring, and control the stirring speed to 25rpm. (2) Turn on the steam in the jacket of the reactor and heat it until bubbles appear on the surface of the liquid material in the reactor. Turn off the steam and use the heat of polymerization to allow the system to heat up naturally to 80-98℃. After the temperature in the reactor rises naturally, the reaction begins. Open the exhaust valve to remove the steam in the jacket and keep the reaction at normal pressure for 3 hours. When the temperature drops below 80℃, heat the jacket to replenish steam once for 1 minute and remove the water in the jacket. (3) After the heat preservation reaction is completed, adjust the stirring speed to 45 rpm, add the neutralizing agent to carry out the neutralization reaction, add it into the reactor at a rate of 21 kg / min, and after the addition is completed, react for 30 min, the degree of neutralization is 73%; (4) After the neutralization reaction is completed, dilution water is added in batches for dilution. Add the first batch of dilution water and stir for 60 minutes. Add the second batch of dilution water and stir for 30 minutes. Add the third batch of dilution water and stir for 30 minutes. Add the fourth batch of dilution water and stir for 30 minutes. The water addition rate should be such that the water and the material in the reactor can be mixed evenly. (5) After dilution, start the reactor jacket water pump and heat exchanger to cool down to below 60°C, add post-treatment aids and stir evenly, pump the material in the reactor into the slurry tank, filter it twice with a 160-mesh filter bag, take a sample for testing, the concentration of the refractometer is 22.1 divisions, the viscosity is 71 cps (30°C), the pH is 6.0, and the material is discharged to obtain a smoothing agent for enhancing the abrasion resistance of textile slurry. Example 2

[0031] The mixture was prepared according to a total monomer weight of 2100 kg. The monomers consisted of the following components by mass percentage: 50% octadecyl methacrylate, 6% acrylic acid, 18% methacrylic acid, 3% styrene, 10% methyl methacrylate, and 13% butyl acrylate. Octadecyl methacrylate was a self-synthesized product. Two batches of synthesized octadecyl methacrylate were used. The first batch was tested and found to contain 82.15% octadecyl methacrylate and 17.85% methacrylic acid. The second batch was tested and found to contain 82.46% octadecyl methacrylate and 17.54% methacrylic acid. These were included in the total amount of methacrylic acid in the formulation, and the amount of methacrylic acid added was reduced accordingly. The reaction medium and auxiliaries were components accounting for the following percentages of the total monomer weight: 32% recycled industrial alcohol, 7% fatty alcohol polyoxyethylene ether penetrant, 5% isooctanol, 0.02% n-dodecyl mercaptan, 0.005% tert-dodecyl mercaptan, 3% water, and 2% peroxide. Benzoyl 1.4%, fatty alcohol polyoxyethylene ether penetrant model R803A, water from the fractionated product, the water and methacrylic acid content in the fractionated product were measured, the water mass content was 54.72%, and the methacrylic acid mass content was 45.28%. The fractionated product was directly recycled into the reaction system, and the methacrylic acid in the fractionated product participated in copolymerization as a supplementary monomer. The amount of methacrylic acid added to the formula was reduced accordingly based on the measurement results; the neutralizing agent was ammonia water, 340 kg of ammonia water was diluted with 1000 kg of process water to make... Use: Add dilution water in 4 batches. The dilution water is hot process water. The amount of dilution water added is 1750 kg for the first batch, 1750 kg for the second batch, 2100 kg for the third batch, and 1000 kg for the fourth batch. The post-treatment aids are defoamer and bactericide. The defoamer is high-temperature resistant defoamer X-18C. Dilute 14 kg of high-temperature resistant defoamer X-18C with 80 kg of process water, stir until completely dissolved, and use immediately. The bactericide is MBS bactericide. Dilute 14 kg of bactericide with 50 kg of process water, stir evenly, and use.

[0032] (1) Check whether the cooling tower is normal and whether the condenser outlet water is normal. If it is normal, start the reaction, put the reaction medium and additives into the reactor, mix the monomers in the monomer mixing tank, add the mixed monomers into the reactor, rinse the pipeline of the 30kg industrial recovered alcohol in the reaction medium and additives in the monomer mixing tank, put the rinse material into the reactor, seal the reactor, start the reactor stirring, and control the stirring speed to 25rpm. (2) Turn on the steam in the jacket of the reactor and heat it until bubbles appear on the surface of the liquid material in the reactor. Turn off the steam and use the heat of polymerization to allow the system to heat up naturally to 80-98℃. After the temperature in the reactor rises naturally, the reaction begins. Open the exhaust valve to remove the steam in the jacket. Keep the reaction at normal pressure for 3 hours. When the temperature drops below 80℃, heat the jacket to replenish steam once for 2 minutes and remove the water from the jacket. (3) After the heat preservation reaction is completed, adjust the stirring speed to 45 rpm, add the neutralizing agent to carry out the neutralization reaction, add it into the reactor at a rate of 21 kg / min, and after the addition is completed, react for 30 min, the degree of neutralization is 65%; (4) After the neutralization reaction is completed, dilution water is added in batches for dilution. Add the first batch of dilution water and stir for 60 minutes. Add the second batch of dilution water and stir for 30 minutes. Add the third batch of dilution water and stir for 30 minutes. Add the fourth batch of dilution water and stir for 30 minutes. The water addition rate should be such that the water and the material in the reactor can be mixed evenly. (5) After dilution, start the reactor jacket water pump and heat exchanger to cool down to below 60°C, add post-treatment aids and stir evenly, pump the material in the reactor into the slurry tank, filter it twice with a 160-mesh filter bag, take a sample for testing, the concentration of the refractometer is 21.6 grids, the viscosity is 35cps (30°C), and the pH is 6.5. Then discharge the material to obtain a smoothing agent for enhancing the abrasion resistance of textile slurry. Example 3

[0033] The mixture was prepared according to a total monomer weight of 2100 kg. The monomers consisted of the following components by mass percentage: octadecyl methacrylate 50%, acrylic acid 6%, methacrylic acid 19%, styrene 2.5%, methyl methacrylate 9%, and butyl acrylate 13.5%. Octadecyl methacrylate was a self-synthesized product. The mass content of octadecyl methacrylate was measured to be 82.46%, and the mass content of methacrylic acid was 17.54%. This was included in the total input of methacrylic acid in the formula, and the amount of methacrylic acid in the formula was reduced accordingly. The reaction medium and auxiliaries were components accounting for the following percentages of the total monomer mass: 32% recovered industrial alcohol, 10% fatty alcohol polyoxyethylene ether penetrant, 3% isooctanol, 0.01% n-dodecyl mercaptan, 0.015% tert-dodecyl mercaptan, 3% water, and 1.4% benzoyl peroxide. The water was obtained from the fractionation product. The water and methacrylic acid content in the fraction was determined, with water accounting for 55.08% by mass and methacrylic acid accounting for 44.92% by mass. The fraction was directly recycled into the reaction system, with the methacrylic acid in the fraction participating in copolymerization as a supplementary monomer. The amount of methacrylic acid added to the formulation was reduced accordingly based on the measurement results. The neutralizing agent was ammonia water, which was diluted with 1000 kg of process water before use. The dilution water was added in three batches, which was hot process water. The amount of dilution water added was 1800 kg for the first batch, 2500 kg for the second batch, and 1700 kg for the third batch. The post-treatment aids were defoamer and bactericide. The defoamer was high-temperature resistant defoamer X-18C, which was diluted with 80 kg of process water and stirred until completely dissolved before use. The bactericide was MBS bactericide, which was diluted with 50 kg of process water and stirred evenly before use.

[0034] (1) Check whether the cooling tower is normal and whether the condenser outlet water is normal. If it is normal, start the reaction, put the reaction medium and auxiliary agent into the reactor, mix the monomers in the monomer mixing tank, add the mixed monomers into the reactor, rinse the pipeline of the 30kg industrial recovered alcohol in the reaction medium and auxiliary agent in the monomer mixing tank, put the rinse material into the reactor, seal the reactor, start the reactor stirring, and control the stirring speed to 25rpm. (2) Turn on the steam in the jacket of the reactor and heat it until bubbles appear on the surface of the liquid material in the reactor. Turn off the steam and use the heat of polymerization to allow the system to heat up naturally to 80-98℃. After the temperature in the reactor rises naturally, the reaction begins. Open the exhaust valve to remove the steam in the jacket and keep the reaction at normal pressure for 3 hours. When the temperature drops below 80℃, heat the jacket to replenish steam once for 1.5 minutes and remove the water from the jacket. (3) After the heat preservation reaction is completed, adjust the stirring speed to 45 rpm, add the neutralizing agent to carry out the neutralization reaction, add it into the reactor at a rate of 21 kg / min, and after the addition is completed, react for 30 min, the degree of neutralization is 69%; (4) After the neutralization reaction is completed, dilution water is added in batches for dilution. Add the first batch of dilution water and stir for 65 minutes. Add the second batch of dilution water and stir for 35 minutes. Add the third batch of dilution water and stir for 35 minutes. The water addition rate should be such that the water and the material in the reactor can be mixed evenly. (5) After dilution, start the reactor jacket water pump and heat exchanger to cool down to below 60°C, add post-treatment aids and stir evenly, pump the material in the reactor into the slurry tank, filter it twice with a 160-mesh filter bag, take a sample for testing, the concentration of the refractometer is 21.9 grids, the viscosity is 52cps (30°C), and the pH is 6.3, then discharge the material to obtain a smoothing agent for enhancing the abrasion resistance of textile slurry. Example 4

[0035] Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in step (2) of Example 4, the temperature is controlled by external heating throughout the process. After the jacket steam is turned on, the heating is continued to keep the temperature of the reaction system at 85°C throughout the process and keep the reaction at this temperature for 3 hours. The sample was tested and the concentration was 21.9 divisions, the viscosity was 110 cps (30°C), and the pH was 6.3. Example 5

[0036] Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, after the neutralization reaction in step (4), dilution water is added to the reactor twice. The first addition is 1 / 3 of the total dilution water, and the mixture is stirred for 60 minutes. The second addition is 2 / 3 of the total dilution water, and the mixture is stirred for 30 minutes. Samples were taken for testing. The concentration on the refractometer was 21.6 divisions, the viscosity was abnormal, and the pH was 6.3. Performance testing experiment

[0037] Sample preparation: Preparation of slurry: Dissolve 5% polyvinyl alcohol, 8% acrylate slurry WJ-68, and 2% smoothing agent sample in deionized water, and add water to make up the balance to 100% to prepare the slurry working solution. Set up a blank control. The slurry working solution contains only 5% polyvinyl alcohol and 8% acrylate slurry WJ-68. A polyester filament simulated silk fabric (polyester low-elasticity yarn 83.3dtex / 36f, plain weave, warp density 800 ends / 10cm, weft density 600 ends / 10cm, fabric weight 120g / m²) was used as the base fabric. It was treated using a one-dip-one-nip process at a liquor ratio of 1:10, temperature of 60℃, and time of 5 minutes, with a nip rate controlled at 90%. The treated fabric was then dried at 130℃ to obtain fabric samples. The raw yarn (polyester low-elasticity yarn 83.3dtex / 36f) was immersed in the working solution at a liquor ratio of 1:10, temperature of 50℃, and time of 10 minutes. After removal, it was dried at 130℃ to obtain yarn samples. Both the fabric and yarn samples were conditioned under standard atmospheric conditions for 24 hours before testing.

[0038] (1) Referring to GB / T 21196.2-2025 "Textiles - Martindale Method for Determination of Abrasion Resistance of Fabrics - Part 2: Determination of Specimen Breakage", the fabric specimen was cut into a circular specimen with a diameter of 38 mm and installed in the upper specimen holder of the Martindale abrasion tester. The lower part was a standard abrasive (wool felt + standard fabric) with a diameter of 140 mm. Under a friction load of 9 kPa, the specimen was moved along the Lissajous pattern trajectory. The specimen was removed every 500 abrasion intervals. After conditioning under standard atmospheric conditions, the total number of abrasion cycles when two or more independent broken yarns appeared on the surface of the specimen was observed and recorded. Each specimen was tested in parallel three times, and the average value was taken after measurement. The results are recorded in Table 1.

[0039] (2) Referring to GB / T 3916-2013 "Determination of breaking strength and elongation at break of single yarn in packaged textiles (CRE method)", samples were randomly selected from the conditioned yarn samples and tested at a tensile speed of 500 mm / min on a constant speed elongation (CRE) type tensile tester. The sample length was 500 mm, the distance between the upper and lower clamps was 250 mm, and the pre-tension was 10 cN. The maximum strength and elongation at break of each yarn were recorded. 50 yarns were tested for each yarn sample, and the average value and coefficient of variation were calculated. The results are recorded in Table 1.

[0040] Table 1. Test results of abrasion resistance, breaking strength, elongation at break, and coefficient of variation. Example 1 48000 448 4.8 28.5 5.5 Example 2 54500 455 4.3 29.6 5.0 Example 3 51000 452 4.5 29.0 5.2 Example 4 38000 441 5.8 27.5 6.8 Example 5 35500 438 6.2 27.1 7.2 Blank control 30000 435 6.5 26.5 7.7 As shown in Table 1, the abrasion resistance of Examples 1-3 exceeded 48,000 cycles, the tensile strength exceeded 448 cN, the coefficient of variation of tensile strength was below 4.8%, the elongation at break exceeded 28.5%, and the coefficient of variation of elongation was below 5.5%. The performance was significantly improved compared to when no smoothing agent was used, demonstrating that the smoothing agent prepared in this application can effectively improve the abrasion resistance and smoothness of the fabric. In Example 4, isothermal heating replaced the natural heating process of adiabatic polymerization. The lack of a reaction exothermic peak to promote the chain transfer reaction resulted in the polymer molecular weight not being effectively controlled and being too high. Simultaneously, the lower reaction temperature led to insufficient initiator decomposition rate and monomer conversion rate, resulting in decreased cohesive strength and continuity of the film, and a decline in performance. In Example 5, reducing the number of water addition batches caused excessively high local water concentration during the reverse inversion process, leading to sudden polymer precipitation and the formation of irreversible gel particles. This resulted in structural defects in the film and a decline in performance.

[0041] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A smoothing agent for enhancing the abrasion resistance of textile sizing agents, characterized in that: The raw materials for preparation include mixed monomers, reaction media and auxiliaries, neutralizing agents, dilution water, and post-treatment auxiliaries. The mixed monomers comprise the following components in weight percentage: Octadecyl methacrylate 45-55% Acrylic acid 4-8% 16-22% methacrylic acid Styrene 1-4% Methyl methacrylate 8-12% Butyl acrylate 10-16%; The sum of the mass percentages of all components is 100%.

2. The smoothing agent for enhancing the abrasion resistance of textile sizing agents according to claim 1, characterized in that: The mixed monomers comprise the following components in weight percentage: 50% octadecyl methacrylate 6% acrylic acid 18-20% methacrylic acid styrene 2-3% 8-10% methyl methacrylate Butyl acrylate 13-14%; The sum of the mass percentages of all components is 100%.

3. The smoothing agent for enhancing the abrasion resistance of textile sizing agents according to claim 1, characterized in that: The reaction medium and auxiliaries comprise components comprising a percentage of the total monomer mass below: 31-33% of industrial alcohol is recovered. Fatty alcohol polyoxyethylene ether penetrants 7-15% Isooctyl alcohol 1-5% n-Dodecanethiol 0-0.02% tert-dodecyl mercaptan 0.005-0.02% Water 2.5-3.5% Benzoyl peroxide 1.2-1.6%.

4. The smoothing agent for enhancing the abrasion resistance of textile sizing agents according to claim 1, characterized in that: The neutralizing agent includes ammonia.

5. The smoothing agent for enhancing the abrasion resistance of textile sizing agents according to claim 1, characterized in that: The post-treatment aids include defoamers and bactericides.

6. A process for preparing a smoothing agent for enhancing the abrasion resistance of textile sizing agents as described in any one of claims 1-5, characterized in that: Includes the following steps: (1) Add the reaction medium and auxiliaries into the reaction apparatus, add the mixed monomers, seal and start stirring, and control the stirring speed to 20-30 rpm; (2) After heating until bubbles appear on the surface of the liquid material in the reaction apparatus, stop heating and use the heat of polymerization to allow the system to heat up naturally. Keep the reaction at room temperature for 2.5-3.5 hours. (3) After the heat preservation reaction is completed, adjust the stirring speed to 40-50 rpm, add the neutralizing agent to carry out the neutralization reaction. After the addition is completed, react for 20-40 minutes, and the degree of neutralization is 65-73%. (4) After the neutralization reaction is complete, dilute with water in batches, stirring well after each addition; (5) After dilution, cool down, add post-treatment aids and stir evenly, filter and discharge to obtain a smoothing agent for enhancing the abrasion resistance of textile sizing agents.

7. The preparation process according to claim 6, characterized in that: In step (2), the system is naturally heated to 80-98°C by using the exothermic polymerization. When the temperature drops below 80°C, it is heated for 1-2 minutes.

8. The preparation process according to claim 6, characterized in that: In step (4), dilution water is added in 3-5 batches. After the first batch is added, stir for 55-65 minutes. After the second batch and each subsequent batch is added, stir for 25-35 minutes.

9. The preparation process according to claim 6, characterized in that: In step (1), the water in the reaction medium and the auxiliary agent comes from the fraction obtained by fractionation, which includes water and methacrylic acid; the preparation process also includes determining the content of methacrylic acid in the fraction, directly recycling the fraction back into the reaction system, and using the methacrylic acid in the fraction as a supplementary monomer to participate in copolymerization, and reducing the amount of methacrylic acid added in the formulation accordingly based on the determination results.

10. The preparation process according to claim 6, characterized in that: In step (1), the octadecyl methacrylate in the mixed monomers is a self-synthesized product, and the octadecyl methacrylate contains methacrylic acid; the preparation process also includes determining the content of methacrylic acid in the octadecyl methacrylate and including it in the total amount of methacrylic acid in the formula, thereby reducing the amount of methacrylic acid in the formula accordingly.